Effect of APOE and CHRNA7 Genotypes on the Cognitive Response to Cholinesterase Inhibitor Treatment at Different Stages of Alzheimer's Disease. (March 2015) - Braga, Ianna Lacerda Sampaio; Silva, Patricia Natalia; Furuya, Tatiane Katsue; Santos, Leonardo Caires; Pires, Belisa Caldana; Mazzotti, Diego Robles; Bertolucci, Paulo Henrique; Cendoroglo, Maysa Seabra; Smith, Marília Cardoso
The loss of cholinergic transmission is considered to be an important cause of Alzheimer's disease (AD). Treatment with acetyl cholinesterase inhibitors (ChEIs) shows benefits; however, great heterogeneity has been observed in patient responses. We evaluated apolipoprotein E ( APOE ) and α7 nicotinic receptor ( CHRNA7 ) single-nucleotide polymorphisms (SNPs) and associated these SNPs with pharmacological responses to ChEIs in a Brazilian population with AD. We studied 177 outpatients using ChEIs, and they were classified as responders and nonresponders according to variation in Mini-Mental State Examination (MMSE) status. The analysis of APOE genotypes showed that patients with the ∊4 allele had a worse response than those without the ∊4 allele. We observed an association between the CHRNA7 T allele and a better response to treatment with ChEIs in patients with mild AD (MMSE ≥ 20). The SNP rs6494223 of CHRNA7 as well as APOE ∊4 could be useful for understanding the response to ChEI treatment in patients with AD.